Guidance and Counselling in Education - Agatha Dianovi; Damayanti Siregar; Indi Mawaddah; Suryaningsih Suryaningsih (World Psychology, 2022)
The Guidance Teacher or counsellor is someone who is responsible for providing guidance and counselling in schools consciously towards the development of student's personalities and abilities both from physical and spiritual aspects so that students are able to live independently and fulfil their various developmental tasks as creatures of God in addition to individual beings and social, moral, religious, and cultural beings. Counselling is an effort to help individuals through a process of personal interaction between counsellors and counsellors so that counsellors are able to understand themselves and their environment, be able to make decisions, and determine goals based on the values they believe in so that counsellor feels happy and effective in his behaviour. Guidance Counselling is in a key position in an educational institution, namely a school institution, as a support for the progress or retreat of the quality of education. The role of guidance and counselling in improving the quality of education is not only limited to academic guidance but also personal, social, intellectual, and value-giving guidance.